Influence of grinding-polishing of natural stone on its shine and lightness shades - Шамрай, Володимир Ігорович; Коробийчук, Валентин Вацлавович (Eastern-European Journal of Enterprise Technologies, 2014)
An important problem of stone processing enterprises is decorativeness control of natural stone products. Among many different methods that allow to change natural stone decorativeness parameters, textured surface finishing is the most common. In the study of products from Pokostivske granodiorite, color and lightness classification was proposed. Depending on the stone surface roughness, a change in the stone lightness and shine was investigated. Using the fine-grained diamond tool, stone sample darkening is achieved by reducing the stone surface roughness. Stone lightness can be adjusted to ensure minimum differences in their future use. Ensuring minimum differences of the polished stone surface is possible for species with the same color and adjusted for a stone with red and blue color (from light to dark); for a stone with blue color (from dark to very dark). In the future, it is important to solve the problem of labeling different types of blocks that will ensure their recognition and selection of the grinding-polishing procedure to provide the desired lightness shade.